Community-Engaged Needs Assessment of Deaf American Sign Language Users in Florida, 2018. (July 2022) - James, Tyler G.; McKee, Michael M.; Sullivan, Meagan K.; Ashton, Glenna; Hardy, Stephen J.; Santiago, Yary; Phillips, David G.; Cheong, JeeWon
Objectives: Deaf American Sign Language (ASL) users comprise a linguistic and cultural minority group that is understudied and underserved in health education and health care research. We examined differences in health risk behaviors, concerns, and access to health care among Deaf ASL users and hearing English speakers living in Florida. Methods: We applied community-engaged research methods to develop and administer the first linguistically accessible and contextually tailored community health needs assessment to Deaf ASL users living in Florida. Deaf ASL users (n = 92) were recruited during a 3-month period in summer 2018 and compared with a subset of data on hearing English speakers from the 2018 Florida Behavioral Risk Factor Surveillance System (n = 12 589). We explored prevalence and adjusted odds of health behavior, including substance use and health care use. Results: Mental health was the top health concern among Deaf participants; 15.5% of participants screened as likely having a depressive disorder. Deaf people were 1.8 times more likely than hearing people to engage in binge drinking during the past month. In addition, 37.2% of participants reported being denied an interpreter in a medical facility in the past 12 months. Conclusion: This study highlights the need to work with Deaf ASL users to develop context-specific health education and health promotion activities tailored to their linguistic and cultural needs and ensure that they receive accessible health care and health education.